How great decisions get made : [10 easy steps for reaching agreement on even the toughest issues] - Maruska, Don (Stanford executive briefings, 2004)
Don Maruska has developed a ten-step plan that helps you break through the corporate gridlock to find lasting solutions on even the toughest issues you face.